Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai di Dinas Lingkungan Hidup Kota Palangka Raya - Sari, Erini Junita; Hanifah, Hanifah; Apriano, Gevin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The type of research used is survey research. Meanwhile, the research approach is a quantitative research used to determine the influence of work discipline and work motivation on employee performance at the Palangka Raya City Environmental Agency. The data collection technique uses the purposive sampling technique based on certain criteria so that as many as 45 people who meet the criteria are obtained. The data collection method is using a questionnaire and analyzed using SPSS. The results of this study are that the variables of work discipline have a positive effect on the performance of employees at the Palangka Raya City Environmental Office. The variable of work motivation has a positive but not partially significant effect on employee performance. Then the influence of work discipline and work motivation of 49.8% on the performance of employees at the Palangka Raya City Environmental Agency. It can be concluded that the value of the work discipline regression coefficient is 0.968 and the work motivation regression coefficient is -0.077 with a significance level of 0.02 < 0.05. This means that simultaneously work motivation does not have a significant effect on employee performance, the value is obtained from the results of the questionnaire data answered by the respondents.